(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This study aimed at identifying the impact of a training program on some anthropometric and physiological variables among the players of basketball team at Mu’tah university. The study sample consisted of (5) players. The researchers used the experimental due to its compatibility to the study nature and objectives. The study used (SPSS) for data analysis. The results revealed that the proposed training program has a positive effect on causing physiological changes in systolic and diastolic blood pressure, heartbeat, and the times of breathing in addition to its role in reducing blood sugar, hematocrit, red blood cells and white blood cells and increasing hemoglobin. The results showed that the training program also contributed to reducing weight and fat ratio in the humerus, abdomen and scapula. The researchers recommended popularizing the program among the coaches of basketball in the various Universities as well as focusing more on the physiological variables that could enhance the performance of players.